Sustainable Village Empowerment: Kuwatan Sadesa Program in Banjaran Wetan Village, West Jawa - Gustiawan, Agung; Ade Cahya Kurniawan (Prospect Publishing, 2024)
Banjaran Wetan Village, Banjaran District, Bandung Regency, West Java Province has potential in the development of coffee plant cultivation and honey bee cultivation. The TJSL Department of PT Pupuk Kujang saw this potential and collaborated with the Cekas Kopi Group since 2022 to hold the Kujang Caring for Forests, Village Prosperity (Kuwatan Sadesa) program. This program seeks to empower the people of Banjaran Wetan Village through a sustainable and innovative approach. The purpose of this program is to maximize the economic use of forests without neglecting environmental conservation, developing cultivated products, and empowering local communities. This program is carried out in Banjaran Wetan Village, Banjaran District, Bandung Regency, West Java Province on a sustainable basis from 2022 to 2026. The Kuwatan Sadesa program has achieved various aspects of sustainability such as financial success, infrastructure improvement, expansion of partnership networks by involving various parties, and individual capacity building. Institutionally, 3 (three) groups have been formed that manage the upstream-downstream process, namely the Chekaz Coffee Farmers Group, the Herbal Production Group, and the Chekaz Kopi Garden Camp and Coffee, which ensure the sustainability and efficiency of the supply chain. At the personal level in the group, there are local heroes and administrators who have been given competency transfer in the fields of administration, finance, and public speaking that contribute to the professionalism and effectiveness of group management.